An Experimental Investigation on Bushing Geometrical Properties and Density in Thermal Frictional Drilling - Demir, Zulkuf; Ozek, Cebeli; Bal, Muhammed (Mdpi, 2018)
In thermal friction drilling (TFD) operations, the geometrical dimensions of bushing shape, height and wall thickness are the most vital consequences, since these increase the connecting length and strength. In this paper, AA7075-T651 aluminum alloys with 2, 4, 6, 8, and 10 mm thicknesses were drilled with the TFD process in order to investigate density, volume ratio, and height and wall thickness of the bushings. The experiments were conducted at constant spindle speed and feed rate conditions by using High Speed Steel (HSS) conical tools of 5, 10, 15, and 20 mm in diameter. It was experimentally found that the bushing height and the wall thickness had a tendency to increase linearly with the increase in both material thickness and tool diameter. The effect of tool diameter was found to have more influence on the measurable values than the thickness of the drilled material. The density of the bushing changed trivially. Approximately 70-75 percent of the evacuated material formed the bushing shape in TFD operations.
Keywords: thermal friction drilling; bushing density; bushing shape; bushing height; bushing volume ratio; bushing wall thickness